Farm Hullaballoo! - Smith, Justine (UK Ladybird, 2011)
Ladybird's Big Noisy Books are lovely, sturdy sound books with colourful illustrations by Paul Nicholls and eight exciting sound buttons. This farm sound book is full of detailed pictures of life on a farm, with labels on each picture to pick out interesting features, giving toddlers the detail they love. All the popular animals are introduced: pigs, cows, sheep, ducks, chickens and horses. Young children who are interested in animals and tractors will love playing with this book, pressing the buttons as they read the story
English stories
2 4
Keywords: English stories